Upaya Meningkatkan Kompetensi Pedagogik Guru Melalui Supervisi Akademik Kolaboratif - Suprapto Suprapto (Jurnal Didaktika Pendidikan Dasar, 2023)
This research was aimed to improve teachers’ pedagogical competence which was carried out in two cycles, each cycle consisted of four stages, namely: planning, action, observation and reflection. The subjects in this study were novice teachers and honorary teachers at UPT SMP Negeri 1 Pagelaran, totalling 19 peoples. The research data was analyzed by employing descriptive statistics, then it was presented in form of tables and diagrams to obtain a clearer understanding of increasing teachers’ pedagogical competence. The results of research showed that after the teachers were given collaborative academic supervision, the teachers’ ability in preparing lesson plan has increased to 39.82%. Furthermore, the teacher's ability in carrying learning has also increased to 40.94%. Collaborative academic supervision has increased teachers' ability in carrying out learning outcomes assessments up to 39.94%. Based on the results of this research, it could be concluded that collaborative academic supervision can improved the pedagogical competence of teachers at UPT SMP Negeri 1 Pagelaran academic year 2022/2023.